Efficacy of semirigid ureterorenoscopy with the use of ureteral acsess sheath in the treatment of impacted ureteral stones: A prospective randomized study - Keskin, Ercument; Erdogan, Abdullah; Karabulut, Ibrahim (Annals of Medical Research, 2021)
Aim: To investigate the advantages of using Ureteral Access Sheat (UAS) with semirigid ureterorenoscopy in patients with impacted ureteral stones. Materials and Methods: One hundred and 22 adult patients that presented to our clinic with the complaint of impacted stones in the middle and upper parts of the ureter and were scheduled for surgical treatment. The procedure was performed without UAS in control group and using UAS in study group. Results: No significant difference was found between the two groups in terms of age, gender, stone disease history, presentation complaint, stone side, size, density and localization, degree of renal hydronephrosis, complications and length of hospital stay. Stone migration, operation time, duration of fluoroscopy, and postoperative additional surgical intervention rates were significantly lower in the UAS group [26.2% (n = 16) vs 11.5% (n = 7), p = 0.037; 35.46 ± 5.3 min vs 25.56 ± 4.2 min, p 0.001, 5.50 ± 0.86 sec vs 3.24 ± 0.69 sec, p 0.001; and 19.7% (n = 12) vs 6.6% (n = 4), p = 0.032, respectively]. The operation was successful in 48 (78.7%) patients in the control group and 57 (93.4%) in the UAS group, with a statistically significant difference (p = 0.019).Conclusion: The use of UAS in the treatment of middle-upper impacted ureteral stones presents as an advantageous method due to the shorter operation time and lower rates of intraoperative stone migration and high success rates of the operation.
Keywords: Impacted ureteral stones; semirigid ureterorenoscopy; ureteral acsess sheath